2004
DOI: 10.1111/j.1365-2370.2004.00487.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of human leukocyte antigen (HLA)‐G polymorphism in normal women and in women with recurrent spontaneous abortions

Abstract: Human leukocyte antigen (HLA)-G is a non-classical class I antigen. It has limited expression, but is high at the foetomaternal interface. This unique expression pattern of HLA-G suggests that it might be important for survival of the foetus during pregnancy. In the present study, 120 women with recurrent spontaneous abortions (RSA) and 120 fertile control women were genotyped for the HLA-G locus. This is the first report describing HLA-G polymorphism in normal fertile and RSA women from India. The allele HLA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 28 publications
5
46
3
Order By: Relevance
“…In agreement with this, G*0102 was first reported by Pook et al [67] and was only identified in a North India female control population with very low frequency (1.2% of 240 chromosomes) [60]. This allele was not detected in African Shona [68], Danish [4], and Brazilian [69] populations, however, shedding some doubt on the true existence of this variant [68,70].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In agreement with this, G*0102 was first reported by Pook et al [67] and was only identified in a North India female control population with very low frequency (1.2% of 240 chromosomes) [60]. This allele was not detected in African Shona [68], Danish [4], and Brazilian [69] populations, however, shedding some doubt on the true existence of this variant [68,70].…”
Section: Discussionsupporting
confidence: 78%
“…In addition, HLA-G polymorphism has been linked to pathological situations, such as pemphigus vulgaris [52], inflammatory bowel disease [53], sarcoidosis [54], and idiopathic dilated cardiomyopathy [55]. The overall picture emerging from different independent studies is that some HLA-G polymorphism also is associated with complications of pregnancy, such as implantation failure during in vitro fertilization (IVF) [47], recurrent spontaneous abortion (RSA) [56][57][58][59][60][61], and PE [45,62,63]. Nonetheless, some of these associations are controversial.…”
Section: Introductionmentioning
confidence: 99%
“…In particular the HLA-G 14 bp ins allele decreases mRNA stability [78] and protein production [2,51,[79][80][81]. RSA is associated with the presence of an increased frequency of women heterozygous [82,83] or homozygous for the 14 bp ins allele [OR 2.7; 95% confidencial interval (CI) = 1.1-6.5; p = 0.03] [80,84] in comparison with controls. Hviid et al [84] have shown more RSA women carrying the G*0106 allele (16%), characterized by the presence of the 14 bp insertion, compared to controls (2%).…”
Section: Pathological Conditionsmentioning
confidence: 99%
“…Psychological factors [9] and familial predisposition [10] have been claimed as well. Currently, human leukocyte antigen (HLA)-G polymorphism [11], elevated plasma tumor necrosis factor (TNF)-alpha levels [12], and abnormal expression of CD56+ cells by the endometrium [13] have also been related to recurrent spontaneous abortions. Generally, more than one etiologic factor is present in the same case.…”
Section: Introductionmentioning
confidence: 99%